Study of bacteriological profile in chronic suppurative otitis media and their pattern of antibiotic sensitivity - Shinde, Kiran J.; Pathak, Netra A.; Katake, Namrata J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic suppurative otitis media is a long-standing infection of the middle ear cleft which is characterized by recurrent and persistent ear discharge and persistent non healing perforation of tympanic membrane. It can lead to severe complications if not treated appropriately. Due to emerging antibiotic resistance, it is necessary to understand the antimicrobial pattern and their sensitivity to antibiotics which will help clinicians to select antibiotic which is sensitive to their corresponding microorganism. The aim of the study is to isolate the prevalent microorganism and study their antibiotic sensitivity pattern in patients of chronic suppurative otitis media (CSOM). Methods: Total 100 patients were examined, ear swab were collected by sterile ear swab and sent for microscopy and culture sensitivity examination to microbiology department. Results were documented and analyzed. Results: Pseudomonas aeruginosa was the most common isolate (41%) followed by Staphylococci (28.2%). Gram negative cocci showed high degree of sensitivity to Cotrimoxazole (100%), Amikacin (79%) and Piperacillin - tazobactum (75%). Gram positive cocci showed high degree of sensitivity to Linezolid. Conclusions: Study of bacteriological profile and their sensitivity pattern helps in empirical therapy and reduces the risk of complications.